2016
DOI: 10.1016/j.athoracsur.2015.10.092
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Versus Bioprosthetic Aortic Valve Replacement in Middle-Aged Adults: A Systematic Review and Meta-Analysis

Abstract: The choice of a bioprosthetic valve (BV) or mechanical valve (MV) in middle-aged adults undergoing aortic valve replacement is a complex decision that must account for numerous prosthesis and patient factors. A systematic review and meta-analysis was performed to compare long-term survival, major adverse prosthesis-related events, anticoagulant-related events, major bleeding, reoperation, and structural valve degeneration in middle-aged patients receiving a BV or MV. A comprehensive search from six electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
72
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 38 publications
2
72
1
2
Order By: Relevance
“…La relación riesgo/beneficio entre estas dos opciones es el fundamento para el uso de prótesis mecánica en pacientes menores de 50 años, según recomendación de la American Heart Association (AHA) (2) , o menores de 60 años según recomendación de la European Society of Cardiology (ESC) (3) (ambas indicaciones IIa). El uso de bioprótesis ha aumentado significativamente en las últimas décadas en todos los grupos de edad (4) .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…La relación riesgo/beneficio entre estas dos opciones es el fundamento para el uso de prótesis mecánica en pacientes menores de 50 años, según recomendación de la American Heart Association (AHA) (2) , o menores de 60 años según recomendación de la European Society of Cardiology (ESC) (3) (ambas indicaciones IIa). El uso de bioprótesis ha aumentado significativamente en las últimas décadas en todos los grupos de edad (4) .…”
Section: Introductionunclassified
“…A nivel internacional existen trabajos recientes en los cuales se comparan los resultados a largo plazo en pacientes con bioprótesis y prótesis mecáni-ca (4) . En contraste con este cuerpo de evidencia en la literatura internacional, no existen datos nacionales al respecto.…”
Section: Introductionunclassified
“…Two types of stents are used commonly for PCI; bare-metal stent and drug-eluting stent (Brodie, et al 2008). Many studies have reported that cessation of antiplatelet medications produces in-stent thrombosis in patients, O., & Bland, M. 2006) (Zhao, D. F., et al 2016). Mechanical valves are thrombogenic and therefore require life-long anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Biologic valves (porcine, bovine, equine) have the advantage of not requiring life-long anticoagulation, but the significant disadvantage of valve deterioration requiring reintervention generally within 15-20 years (if not earlier). To make the decision between these two options more difficult, several recent studies have shown that balancing the risk-benefit ratio between these two choices in the young patient is complicated (1,2). Although the risk of reoperative AVR in the setting of a deteriorated bioprosthetic valve is higher than in the initial operation, the cumulative risk of anticoagulation, thrombosis, thromboembolism and other valve-related complications associated with a mechanical valve, make the life-time risks of valve associated morbidity and mortality for a young patient in need of an AVR relatively equal with these two options (2).…”
mentioning
confidence: 99%
“…To make the decision between these two options more difficult, several recent studies have shown that balancing the risk-benefit ratio between these two choices in the young patient is complicated (1,2). Although the risk of reoperative AVR in the setting of a deteriorated bioprosthetic valve is higher than in the initial operation, the cumulative risk of anticoagulation, thrombosis, thromboembolism and other valve-related complications associated with a mechanical valve, make the life-time risks of valve associated morbidity and mortality for a young patient in need of an AVR relatively equal with these two options (2). The recent introduction of percutaneous valve-in-valve AVR technology makes the advantage of not requiring anticoagulation even more attractive for the tissue AVR.…”
mentioning
confidence: 99%